Additive Effect of Parathyroid Hormone and Zoledronate Acid on Prevention Particle Wears-Induced Implant Loosening by Promoting Periprosthetic Bone Architecture and Strength in an Ovariectomized Rat Model - Zhou, Chenhe; Wang, Yangxin; Meng, Jiahong; Yao, Minjun; Xu, Huikang; Wang, Cong; Bi, Fanggang; Zhu, Hanxiao; Yang, Guang; Shi, Mingmin; Yan, Shigui; Wu, Haobo (Frontiers in Endocrinology, 2022)
Implant-generated particle wears are considered as the major cause for the induction of implant loosening, which is more susceptible to patients with osteoporosis. Monotherapy with parathyroid hormone (PTH) or zoledronate acid (ZOL) has been proven efficient for preventing early-stage periprosthetic osteolysis, while the combination therapy with PTH and ZOL has exerted beneficial effects on the treatment of posterior lumbar vertebral fusion and disuse osteopenia. However, PTH and ZOL still have not been licensed for the treatment of implant loosening to date clinically. In this study, we have explored the effect of single or combined administration with PTH and ZOL on implant loosening in a rat model of osteoporosis. After 12 weeks of ovariectomized surgery, a femoral particle-induced periprosthetic osteolysis model was established. Vehicle, PTH (5 days per week), ZOL (100 mg/kg per week), or combination therapy was utilized for another 6 weeks before sacrifice, followed by micro-CT, histology, mechanical testing, and bone turnover examination. PTH monotherapy or combined PTH with ZOL exerted a protective effect on maintaining implant stability by elevating periprosthetic bone mass and inhibiting pseudomembrane formation. Moreover, an additive effect was observed when combining PTH with ZOL, resulting in better fixation strength, higher periprosthetic bone mass, and less pseudomembrane than PTH monotherapy. Taken together, our results suggested that a combination therapy of PTH and ZOL might be a promising approach for the intervention of early-stage implant loosening in patients with osteoporosis.